Design and Build Customer Complain Applications for Mobile Based MVVM Architecture Method - Alexius Hendra Gunawan; Andri Wijaya; Dellih Wijaya (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Abstract PT. DhanaJaya BogaIndo has more than twenty restaurants spread across Jakarta, Surabaya and Australia. At present complaints regarding services and food served are still being done by providing limited criticism and suggestions during operational hours, so employees in the service section always record complaints and suggestions from customers who come to restaurants are accommodated, then convey related to food, service and the environment dirty one. related to customer complaints. Information on customer complaints can be received directly by management, so actions can be taken quickly.